Krishna
0

Step 1: Substitute either values slope(m) and any one point into the equation of a straight line.

NOTE:  Take the point as (0, 0)

            FORMULA: Equation of a straight line

                               y - y_1 = m(x - x_1)

                            Where m = slope and ( x_1, y_1) = any point


            EXAMPLE: I took (2, 0) as a point and m = \frac{4}{5}

                                         y - 0 = \frac{4}{5} ( x - 2)

                                            5y = 4x - 8

Step 2: Simplify and make the equation in the form of Ax + By + C =  0